A New Unconstrained Approach to GNSS Atmospheric Water Vapor Tomography. Issue 17 (29th August 2021) - Miranda, P. M. A.; Mateus, P.
Abstract: A new atmospheric tomographic model totally based on Global Navigation Satellite System (GNSS) observations is proposed and tested against field observations. The method does not require a first guess, does not contain specific constraints on the variability of water vapor density inside the tomographic domain, and is able to produce reasonable results at 6 km horizontal and 500 m vertical resolutions, from short (30 min) GNSS data samples. The inversion method uses the Moore‐Penrose pseudoinverse, which is made possible by increasing the rank of the design matrix through angular interpolation and extrapolation of the observations. Comparisons against 30 consecutive 4‐h radiosonde observations and model simulations suggest the ability of the method to detect inversions and local maxima aloft, and behave sensibly in the far‐field. Further improvements from this method may be expected from higher density and multi‐constellation networks. Plain Language Summary: Knowing the three‐dimensional distribution of water vapor is a key goal of atmospheric observation that has been very difficult to attain, given its space and time variability. A new method of water vapor tomography is proposed, exclusively based on Global Navigation Satellite System observations, such as GPS, which is found to lead to sensible results. These results suggest a feasible tomographic system, using data from all satellite constellations (GPS, Glonass, Beidou, and Galileo) with a dense network of ground stations. Key Points: Reasonable water vapor density profiles may be obtained by Global Navigation Satellite System tomography without extra data or constraints The new method is able to detect inversions and secondary maxima aloft, suggesting its potential for boundary layer characterization The method requires dense networks but may be optimized for fast inversions in fixed geometry setups